Cellular Response to the high protein digestibility/high-Lysine (hdhl) sorghum mutation. (December 2015) - Benmoussa, Mustapha; Chandrashekar, Arun; Ejeta, Gebisa; Hamaker, Bruce R.
Highlights: 2D-Gel analysis didn't show any apparent kafirin subunit molecular change. Identified up and down regulated non-kafirin proteins were involved in different biochemical synthesis pathways. Western blot analysis confirmed a high expression of chaperones in the hdhl mutant. A decrease in γ-kafirin subunits contents in the hdhl mutant. An increase in the 22 kDa α-kafirin content in the hdhl mutant. Abstract: A high protein digestibility/high-lysine mutant P721Q ( hdhl ) with a multi-folded protein body morphology has been developed, with a 22 kDa α-kafirin single point mutation having also been recently identified. Relatively little is known regarding the resulting cellular response in hdhl endosperm. The aim is to elucidate these biochemical changes. Two-dimentional gel electrophoresis showed an apparent increase of non-kafirin and a decrease in kafirins content in hdhl endosperm. Mass spectrometry data yielded the identity of differentially expressed non-kafirin proteins in hdhl, wild-type lines such as cytoskeleton and chaperones proteins, and also others involved in amino acids and carbohydrates biochemical synthesis pathways. Western blot analysis showed that chaperone proteins were more highly expressed in the hdhl than the wild-type sorghum and confirmed the non-kafirin proteins proteomic results. Two-dimentional gel electrophoresis showed that the γ-kafirin subunits content had decreased, and the 22 kDa α-kafirin subunit was increased in hdhl without any apparent molecular mass change. The observed differential expression most likely led to proteins interactions between γ- and α-kafirin subunits in particular, which resulted in a kafirins packing differently to form the protein body's multi-folded morphology, while also improving its digestibility.